Life balance is fiction : finding your passion will bring a life built to last - Porras, Jerry I. (Pearson Education Pub. as FTPress Delivers, 2010)
"This Element is an excerpt from Success built to last: creating a life that matters (ISBN: 9780132287517) by Jerry Porras, Stewart Emery, and Mark Thompson. As conventionally defined, "balance" doesn't matter. Passion does. Learn how to find it--and start living it!"--Resource description page.